Analysis of Geothermal Well 'X' Productivity at Kamojang Using PTS Survey Before and After Broaching Method : A Case Study from Kamojang Geothermal Field, Indonesia - Bima Aditya Octavian Bima Aditya Octavian; Ir. Riska Laksmita Sari, S.Si., M.T. Riska Laksmita Sari (Journal of Petroleum and Geothermal Technology, 2026)
The decline in geothermal well performance remains one of the most persistent challenges in sustaining steam supply within vapor-dominated fields. Well X in the Kamojang Geothermal Field experienced a significant productivity drop caused by severe wellbore constriction due to composite scale consisting of silica minerals (Quartz and Tridymite) and iron oxides (Magnetite and Hematite). This study evaluates the effectiveness of the broaching method in restoring well deliverability through comparative analysis of Pressure-Temperature-Spinner (PTS) surveys conducted before and after intervention. PTS profiles were used to identify feedzone contributions, diameter reduction, fluid velocity anomalies, thermodynamic behavior, and mass flow degradation. Steam-table-based calculations were applied to determine fluid density and mass flow rate, followed by computation of the Productivity Index (PI). The results show that scale accumulation reduced the effective wellbore diameter from 0.32 m to 0.16 m, lowering mass flow from 3.56 kg/s to 1.77 kg/s and decreasing PI to 0.09 kg/s/bar. Mechanical broaching successfully removed the composite scale, restoring the diameter to 0.32 m, increasing mass flow to 3.56 kg/s, and improving PI to 0.31 kg/s/bar—equivalent to a 240% enhancement. The findings confirm that broaching is an efficient, low-cost intervention capable of recovering lost productivity without requiring chemical stimulation or drilling a new well, offering significant operational and economic benefits for geothermal field management.